Search capital - Carlos Carrillo-Tudela; Eric Smith (Institute for the Study of Labor (IZA), 2012)
We construct a simple equilibrium search model in which workers accumulate information about previously met employment contacts. We term the latter search capital. Here search capital (partially) insures workers against adverse shocks. The model provides a theory of job-to-job transitions that are associated with voluntary or involuntary mobility and with wage rises or wage cuts. It also shows why low wage and younger workers are associated with a higher probability of becoming unemployed.
urn:nbn:de:101:1-201206146314
Keywords: J62; J63; J64; 330; search capital; turnover; wage cuts; Arbeitsuche; Arbeitsmobilität; Informationsverhalten; Lohnstruktur; Theorie